Xanthogen compound dispersion, conjugated diene polymer latex composition, film molded article, dip molded article, and adhesive composition
Patent Information
- Application Number
- JP2021567394
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-18
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-12-18
AI Technical Summary
【0009】 本発明によれば、共役ジエン系重合体などの重合体の加硫促進剤として用い、ディップ成形体などの膜成形体とした場合に、即時型アレルギー(Type I)に加えて遅延型アレルギー(Type IV)の症状の発生を抑制可能であり、しかも、得られるディップ成形体などの膜成形体を、引張強度および引裂強度に優れ、かつ、引張強度および引裂強度の安定性に優れたものとすることができるキサントゲン化合物分散体、ならびに、このようなキサントゲン化合物分散体を用いて得られる共役ジエン系重合体ラテックス組成物、およびこのような共役ジエン系重合体ラテックス組成物からなる膜成形体、ディップ成形体、および接着剤組成物を提供することができる。
Smart Images

Figure 0007632306000001 
Figure 0007632306000002 
Figure 0007632306000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a xanthogen compound dispersion, a conjugated diene polymer latex composition, a film molding, a dip molded product, and an adhesive composition; more particularly, the present invention relates to a xanthogen compound dispersion which, when used as a vulcanization accelerator for a polymer such as a conjugated diene polymer to form a film molding such as a dip molded product, can suppress the occurrence of symptoms of immediate-type allergy (Type I) as well as delayed-type allergy (Type IV), and further, can make the obtained film molding such as a dip molded product excellent in tensile strength and tear strength and excellent in stability of tensile strength and tear strength; a conjugated diene polymer latex composition obtained by using such a xanthogen compound dispersion; and a film molding, a dip molded product, and an adhesive composition each comprising such a conjugated diene polymer latex composition. [Background technology]
[0002] It has been known that latex compositions containing natural rubber latex are dip molded to obtain dip molded articles such as nipples, balloons, gloves, balloons, and sacks that are used in contact with the human body. However, natural rubber latex contains proteins that cause immediate-type allergy (Type I) symptoms in the human body, and therefore may be problematic as a dip molded article that comes into direct contact with the mucous membranes or organs of the body. Therefore, the use of synthetic rubber latex instead of natural rubber latex has been investigated.
[0003] For example, Patent Document 1 discloses a latex composition for dip molding, which is made by compounding zinc oxide, sulfur, and a vulcanization accelerator with synthetic polyisoprene latex, which is a synthetic rubber. However, while the technology of Patent Document 1 can prevent the occurrence of immediate-type allergies (Type I) caused by proteins derived from natural rubber, when a dip molded article is made, the vulcanization accelerator contained in the dip molded article can cause delayed-type allergy (Type IV) symptoms when the article comes into contact with the human body. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2014 / 129547 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a xanthogen compound dispersion which, when used as a vulcanization accelerator for a polymer such as a conjugated diene polymer to form a film molded product such as a dip molded product, can suppress the occurrence of symptoms of immediate-type allergy (Type I) as well as delayed-type allergy (Type IV), and can provide a film molded product such as a dip molded product having excellent tensile strength and tear strength and excellent stability of the tensile strength and tear strength; a conjugated diene polymer latex composition obtained by using such a xanthogen compound dispersion; and a film molded product, a dip molded product, and an adhesive composition obtained by using such a conjugated diene polymer latex composition. [Means for solving the problem]
[0006] As a result of intensive research into solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by a xanthogen compound dispersion containing a xanthogen compound, an anionic surfactant not having a polyoxyalkylene structure, a nonionic surfactant, and water or alcohol, and have completed the present invention based on this finding.
[0007] That is, according to the present invention, there is provided a xanthogen compound dispersion containing a xanthogen compound, an anionic surfactant not having a polyoxyalkylene structure, a nonionic surfactant, and water or an alcohol. In the xanthogen compound dispersion of the present invention, the ratio of the anionic surfactant not having a polyoxyalkylene structure to the nonionic surfactant is preferably 99:1 to 10:90 in terms of the weight ratio of "anionic surfactant not having a polyoxyalkylene structure:nonionic surfactant". In the xanthogen compound dispersion of the present invention, the anionic surfactant having no polyoxyalkylene structure is preferably an aromatic compound. In the xanthogen compound dispersion of the present invention, the nonionic surfactant preferably has a number average molecular weight of 100 to 5,000.
[0008] According to the present invention, there is also provided a conjugated diene polymer latex composition containing a latex of a conjugated diene polymer, a vulcanizing agent, and the xanthogen compound dispersion of the present invention. The conjugated diene polymer latex composition of the present invention preferably further contains a metal oxide and / or a typical metal compound. In the conjugated diene polymer latex composition of the present invention, the conjugated diene polymer is preferably synthetic polyisoprene, a styrene-isoprene-styrene block copolymer, or deproteinized natural rubber. Furthermore, according to the present invention, there are provided a film-formed article made of such a conjugated diene polymer latex composition, and a film-formed article, a dip-formed article, and an adhesive composition made of such a conjugated diene polymer latex composition. Effect of the Invention
[0009] According to the present invention, there can be provided a xanthogen compound dispersion which, when used as a vulcanization accelerator for a polymer such as a conjugated diene polymer and formed into a film molded product such as a dip molded product, can suppress the occurrence of symptoms of delayed-type allergy (Type IV) in addition to immediate-type allergy (Type I), and can provide a film molded product such as a dip molded product having excellent tensile strength and tear strength and excellent stability of the tensile strength and tear strength, as well as a conjugated diene polymer latex composition obtained by using such a xanthogen compound dispersion, and a film molded product, a dip molded product, and an adhesive composition each comprising such a conjugated diene polymer latex composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Xanthogen compound dispersion> The xanthogen compound dispersion of the present invention contains a xanthogen compound, an anionic surfactant not having a polyoxyalkylene structure, a nonionic surfactant, and water or an alcohol.
[0011] The xanthogen compound used in the present invention is a compound that acts as a vulcanization accelerator, and therefore the xanthogen compound dispersion of the present invention can be suitably used as a vulcanization accelerator for polymers such as conjugated diene polymers. The xanthogen compound acts as a vulcanization accelerator during vulcanization, and after vulcanization, it is decomposed into alcohol, carbon disulfide, etc. by heat applied during vulcanization. In addition, the alcohol, carbon disulfide, etc. generated by the decomposition usually volatilize due to heat applied during vulcanization, and this makes it possible to reduce the amount of residual xanthogen compound in the vulcanized product of the obtained polymer such as a conjugated diene polymer. Therefore, according to the present invention, the content of allergy-causing substances in the vulcanized product (e.g., film molded product such as dip molded product) of the obtained polymer such as a conjugated diene polymer can be reduced by using the xanthogen compound dispersion of the present invention without using a vulcanization accelerator (e.g., thiuram vulcanization accelerator, dithiocarbamate vulcanization accelerator, thiazole vulcanization accelerator, etc.) which has conventionally been a cause of the occurrence of delayed-type allergy (Type IV) symptoms, and therefore the occurrence of delayed-type allergy (Type IV) symptoms can be suppressed in addition to immediate-type allergy (Type I).
[0012] The xanthogen compound used in the present invention is not particularly limited, but examples thereof include xanthogenic acid and xanthogenate salts.
[0013] The xanthogenate may be any salt compound having a xanthogenic acid structure, and is not particularly limited. However, metal salts of xanthogenic acid are preferred, and among these, compounds represented by the general formula (ROC(=S)S)xZ (wherein R is a straight-chain or branched hydrocarbon, Z is a metal atom, and x is a number matching the valence of Z, usually 1 to 4, preferably 2 to 4, and particularly preferably 2) are preferred. Furthermore, among metal salts of xanthogenic acid, zinc salts of xanthogenic acid are more preferred.
[0014] The xanthogenate represented by the above general formula (ROC(=S)S)xZ is not particularly limited, and examples thereof include zinc dimethylxanthogenate, zinc diethylxanthogenate, zinc dipropylxanthogenate, zinc diisopropylxanthogenate, zinc dibutylxanthogenate, zinc dipentylxanthogenate, zinc dihexylxanthogenate, zinc diheptylxanthogenate, zinc dioctylxanthogenate, zinc di(2-ethylhexyl)xanthogenate, zinc didecylxanthogenate, zinc didodecylxanthogenate, potassium dimethylxanthogenate, potassium ethylxanthogenate, potassium propylxanthogenate, potassium isopropylxanthogenate, potassium butylxanthogenate, and potassium pentylxanthogenate. Examples of suitable xanthates include potassium xanthate, potassium hexyl xanthate, potassium heptyl xanthate, potassium octyl xanthate, potassium 2-ethylhexyl xanthate, potassium decyl xanthate, potassium dodecyl xanthate, sodium methyl xanthate, sodium ethyl xanthate, sodium propyl xanthate, sodium isopropyl xanthate, sodium butyl xanthate, sodium pentyl xanthate, sodium hexyl xanthate, sodium heptyl xanthate, sodium octyl xanthate, sodium 2-ethylhexyl xanthate, sodium decyl xanthate, and sodium dodecyl xanthogenate. Among these, isopropyl xanthogenates and butyl xanthogenates may be used, and xanthogenates in which x is 2 or more in the above general formula (ROC(=S)S)xZ are preferred, diisopropyl xanthogenates and dibutyl xanthogenates are more preferred, zinc diisopropyl xanthogenate and zinc dibutyl xanthogenate are even more preferred, and zinc diisopropyl xanthogenate is particularly preferred.
[0015] These xanthogen compounds may be used alone or in combination of two or more.
[0016] The xanthogen compound used in the present invention is dispersed in the xanthogen compound dispersion in the form of particles or powder.
[0017] The volume average particle diameter of the xanthogen compound in the xanthogen compound dispersion is preferably in the range of 0.001 to 9 μm, more preferably in the range of 0.05 to 7 μm, further preferably in the range of 0.05 to 5 μm, and particularly preferably in the range of 0.07 to 3 μm. By setting the volume average particle diameter in the above range, the dispersibility of the xanthogen compound in the xanthogen compound dispersion can be improved. In addition, by setting the volume average particle diameter in the above range, when the xanthogen compound dispersion of the present invention is used as a vulcanization accelerator for a polymer such as a conjugated diene polymer to form a film molded product such as a dip molded product, the obtained film molded product such as a dip molded product can be excellent in tensile strength and tear strength, and excellent in stability of tensile strength and tear strength.
[0018] The 95% volume cumulative diameter (D95) of the xanthogen compound in the xanthogen compound dispersion is preferably in the range of 0.1 to 43 μm, more preferably in the range of 0.1 to 40 μm, even more preferably in the range of 0.1 to 35 μm, and particularly preferably in the range of 0.1 to 20 μm. By setting the 95% volume cumulative diameter (D95) in the above range, the obtained film molded product such as a dip molded product can be made to have excellent tensile strength and tear strength, and excellent stability of the tensile strength and tear strength. The volume average particle diameter and 95% volume cumulative diameter (D95) of the xanthogen compound can be measured, for example, using a laser diffraction scattering type particle size distribution meter.
[0019] The content of the xanthogen compound in the xanthogen compound dispersion of the present invention is preferably 1 to 60% by weight, more preferably 10 to 50% by weight, further preferably 20 to 50% by weight, and particularly preferably 30 to 50% by weight, based on the total weight of the xanthogen compound dispersion. By setting the content of the xanthogen compound within the above range, the xanthogen compound dispersion can be made to have excellent storage stability.
[0020] The xanthogen compound dispersion of the present invention contains, in addition to the above-mentioned xanthogen compound, an anionic surfactant and a nonionic surfactant not having a polyoxyalkylene structure, and is a dispersion obtained by dispersing these in water or alcohol.
[0021] Xanthogen compounds are solid at room temperature and do not dissolve in water or alcohol, and are therefore usually used in a powdered state. However, when a powdered xanthogen compound is blended into a latex composition containing a polymer such as a conjugated diene polymer, the compound tends to have insufficient dispersibility, and therefore has a problem in that it cannot fully exert its effect as a vulcanization accelerator.
[0022] In addition, when such a xanthogen compound is used as a vulcanization accelerator, and is mixed with a latex of a polymer such as a conjugated diene polymer to prepare a latex composition and produce a film molded body such as a dip molded body, it is desirable to continuously produce a large number of film molded bodies such as a dip molded body using the same latex composition from the viewpoint of production efficiency. In this case, the same latex composition is used for several days. On the other hand, when the same latex composition is used for several days, when several days have passed since the start of use, the maturation (pre-vulcanization) of the latex composition progresses, and therefore, the film molded body obtained using the latex composition after several days of use may have a significantly reduced tensile strength and tear strength compared to the film molded body obtained immediately after the start of use, and there was a problem that the stability (maturing stability) of the tensile strength and tear strength of the obtained film molded body is insufficient.
[0023] In order to solve these problems, the present inventors have conducted extensive research and found that a xanthogen compound dispersion containing a xanthogen compound, an anionic surfactant not having a polyoxyalkylene structure, a nonionic surfactant, and water or alcohol can provide a dispersion in which the xanthogen compound is well dispersed, and that a latex composition in which the xanthogen compound is well dispersed can be obtained by mixing the latex of a conjugated diene polymer and a vulcanizing agent in such a dispersion state. As a result, it has been found that the obtained film molded body such as a dip molded body can be excellent in tensile strength and tear strength, and can also be excellent in stability of tensile strength and tear strength. In particular, the xanthogen compound dispersion of the present invention has excellent aging stability when made into a latex composition, so that even if the latex composition is used for a long period of time, it is possible to produce a film molded body such as a dip molded body without extremely decreasing the tensile strength and tear strength, which contributes to improving the production efficiency of a film molded body such as a dip molded body.
[0024] The anionic surfactant having no polyoxyalkylene structure used in the present invention is not particularly limited as long as it is an anionic compound having no polyoxyalkylene structure. From the viewpoint of improving the dispersibility of the xanthogen compound, however, aromatic compounds such as aromatic sulfonic acid compounds and aromatic carboxylic acid compounds are preferred, and aromatic sulfonic acid compounds are more preferred.
[0025] As the anionic surfactant having no polyoxyalkylene structure, an aromatic sulfonic acid compound represented by the following general formula (1) is preferred. [ka] (In the above general formula (1), R 1 and R 2 are each independently a hydrogen atom or any organic group, M +is a monovalent cation. 1 and R 2 may be bonded to each other to form a ring structure.
[0026] In the above general formula (1), M + is a monovalent cation, and is not particularly limited, but may be H + , alkali metal ions, Ag + , Cu + , NH4 + is preferred, alkali metal ions are more preferred, Na + , K + More preferably, Na + is particularly preferred.
[0027] R 1 and R 2 When they are not bonded to each other, R 1 and R 2 Examples of the organic group that can be the aryl group include, but are not limited to, alkyl groups having 1 to 30 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, t-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups; cycloalkyl groups having 3 to 30 carbon atoms, such as cyclopropyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups; aryl groups having 6 to 30 carbon atoms, such as phenyl, biphenyl, naphthyl, and anthranyl groups; and alkoxy groups having 1 to 30 carbon atoms, such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, t-butoxy, n-pentyloxy, n-hexyloxy, and phenoxy groups. These organic groups may have a substituent, and the position of the substituent may be any position.
[0028] Also, R 1 and R 2When they are bonded to each other to form a ring structure, the ring structure is not particularly limited, but is preferably an aromatic compound, more preferably an aromatic compound having a benzene ring such as benzene or naphthalene, and particularly preferably naphthalene. Note that these ring structures may have a substituent, and the position of the substituent may be any position.
[0029] As the anionic surfactant having no polyoxyalkylene structure, among the aromatic sulfonic acid compounds represented by the above general formula (1), the following is particularly preferred: 1 and R 2 are bonded to each other to form a ring structure, forming a benzene ring structure in the above general formula (1). More specifically, it is preferable to use a compound having a structure represented by the following general formula (2). [ka] (In the above general formula (2), R 3 is a divalent hydrocarbon group which may have a substituent, M + is a monovalent cation.)
[0030] In the above general formula (2), M + is a monovalent cation, and is not particularly limited, but may be H + , alkali metal ions, Ag + , Cu + , NH4 + is preferred, alkali metal ions are more preferred, Na + , K + More preferably, Na + is particularly preferred.
[0031] In the above general formula (2), R 3 is not particularly limited as long as it is a divalent hydrocarbon group which may have a substituent, but is preferably an alkylene group having 1 to 10 carbon atoms, and particularly preferably a methylene group.
[0032] The anionic surfactant having no polyoxyalkylene structure preferably has a repeating structure represented by the above general formula (2). The number of repeating units of the structure represented by the above general formula (2) is not particularly limited, but is preferably 10 to 100, more preferably 20 to 50.
[0033] In addition, the anionic surfactants not having a polyoxyalkylene structure include those having a sulfonic acid ionic group (-SO3 - ) to a carboxylate ionic group (-COO - In this case, an aromatic carboxylic acid compound in which R in the above general formula (1) is replaced by 1 and R 2 and R in the above general formula (2) 3 is the same as above.
[0034] Furthermore, the anionic surfactant not having a polyoxyalkylene structure used in the present invention is not limited to those mentioned above, and examples thereof that can be used include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, and sodium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium cetylbenzenesulfonate, and potassium cetylbenzenesulfonate; alkylsulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctyl sulfosuccinate; alkyl sulfate ester salts such as sodium lauryl sulfate and potassium lauryl sulfate; and monoalkyl phosphates such as sodium lauryl phosphate and potassium lauryl phosphate.
[0035] The weight average molecular weight (Mw) of the anionic surfactant having no polyoxyalkylene structure used in the present invention is preferably 200 to 20,000, more preferably 400 to 10,000. The number average molecular weight (Mn) of the anionic surfactant having no polyoxyalkylene structure used in the present invention is preferably 100 to 5,000, more preferably 200 to 1,000. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the anionic surfactant having no polyoxyalkylene structure are values calculated in terms of standard polystyrene by gel permeation chromatography analysis.
[0036] The content of the anionic surfactant not having a polyoxyalkylene structure in the xanthogen compound dispersion of the present invention is not particularly limited, but is preferably 0.1 to 30 parts by weight, more preferably 1 to 20 parts by weight, further preferably 2 to 18 parts by weight, particularly preferably 3 to 15 parts by weight, and most preferably 5 to 10 parts by weight, relative to 100 parts by weight of the xanthogen compound. By setting the content of the anionic surfactant not having a polyoxyalkylene structure within the above range, the dispersibility of the xanthogen compound in the xanthogen compound dispersion can be further improved, and this can further increase the tensile strength and tear strength of the obtained film molded product such as a dip molded product, and can further increase the stability of the tensile strength and tear strength.
[0037] The nonionic surfactant used in the present invention has a segment that acts as a nonionic surfactant in its molecular main chain. A suitable example of such a segment that acts as a nonionic surfactant is a polyoxyalkylene structure.
[0038] Specific examples of nonionic surfactants include polyoxyalkylene glycols, polyoxyalkylene alkyl ethers, polyoxyalkylene alkyl phenyl ethers, polyoxyethylene styrenated phenyl ethers, polyoxyethylene (hydrogenated) castor oil, polyoxyethylene alkylamines, and fatty acid alkanolamides.
[0039] Examples of the polyoxyalkylene glycol include polyoxyethylene glycol, polyoxypropylene glycol, and polyoxypropylene glycol ethylene oxide adducts such as polyoxyethylene polyoxypropylene glycol.
[0040] Examples of polyoxyalkylene alkyl ethers include linear or branched ethers to which 1 to 50 (preferably 1 to 10) propylene oxides and / or ethylene oxides have been added. Among these, linear or branched ethers to which 1 to 50 (preferably 1 to 10) propylene oxides have been added, linear or branched ethers to which 1 to 50 (preferably 1 to 10) ethylene oxides have been added, linear or branched ethers to which a total of 2 to 50 (preferably 2 to 10) ethylene oxides and propylene oxides have been added in blocks or randomly, and the like. Examples of polyoxyalkylene alkyl ethers include polyoxyethylene oleyl ether, polyoxyethylene octyldodecyl ether, polyoxyethylene dodecyl ether, polyoxyethylene lauryl ether, and the like. Among these, polyoxyethylene oleyl ether and polyoxyethylene octyldodecyl ether are preferred.
[0041] Examples of polyoxyalkylene alkylphenyl ethers include compounds in which 1 to 50 (preferably 1 to 10) propylene oxide and / or ethylene oxide units are added to an alkylphenol. Examples of polyoxyethylene styrenated phenyl ether include ethylene oxide adducts of (mono-, di-, tri-)styrenated phenol, and among these, polyoxyethylene distyrenated phenyl ether, which is an ethylene oxide adduct of distyrenated phenol, is preferred.
[0042] Polyoxyethylene (hydrogenated) castor oil includes ethylene oxide adducts of castor oil or hydrogenated castor oil.
[0043] Examples of fatty acid alkanolamides include lauric acid diethanolamide, palmitic acid diethanolamide, myristic acid diethanolamide, stearic acid diethanolamide, oleic acid diethanolamide, palm oil fatty acid diethanolamide, coconut oil fatty acid diethanolamide, and the like.
[0044] Among nonionic surfactants, nonionic surfactants having a polyoxyalkylene structure are preferred, nonionic surfactants having a polyoxyethylene structure are more preferred, hydrocarbyl ethers of polyoxyethylene are more preferred, polyoxyethylene alkyl ethers and polyoxyethylene distyrenated phenyl ethers are even more preferred, and polyoxyethylene alkyl ethers are particularly preferred. The nonionic surfactants may be used alone or in combination of two or more.
[0045] The nonionic surfactant used in the present invention may be a nonionic anionic surfactant having a segment acting as an anionic surfactant in addition to a segment acting as a nonionic surfactant. The nonionic surfactant used in the present invention is preferably one that does not have a segment acting as an anionic surfactant.
[0046] Examples of nonionic anionic surfactants include compounds represented by the following general formula (3). R 4 -O-(CR 5 R 6 CR 7 R 8 ) n -SO3M (3) (In the above general formula (3), R 4represents an alkyl group having 6 to 16 carbon atoms or an aryl group having 6 to 14 carbon atoms which may be substituted with an alkyl group having 1 to 25 carbon atoms; R 5 ~R 8 are each independently selected from the group consisting of hydrogen and a methyl group, M is an alkali metal atom or an ammonium ion, and n is an integer of 3 to 40.
[0047] Specific examples of the compound represented by the above general formula (3) include polyoxyethylene alkyl ether sulfates such as polyoxyethylene lauryl ether sulfate, polyoxyethylene cetyl ether sulfate, polyoxyethylene stearyl ether sulfate, and polyoxyethylene oleyl ether sulfate; and polyoxyethylene aryl ether sulfates such as polyoxyethylene nonylphenyl ether sulfate, polyoxyethylene octylphenyl ether sulfate, and polyoxyethylene distyryl ether sulfate.
[0048] Among nonionic anionic surfactants, nonionic anionic surfactants having a polyoxyalkylene structure are preferred, and nonionic anionic surfactants having a polyoxyethylene structure are more preferred. The nonionic anionic surfactants may be used alone or in combination of two or more.
[0049] The number average molecular weight (Mn) of the nonionic surfactant used in the present invention is preferably 100 to 5000, more preferably 150 to 3500, further preferably 180 to 2500, and particularly preferably 200 to 1000. The number average molecular weight of the nonionic surfactant can be determined as the number average molecular weight in terms of standard polystyrene, for example, by dissolving the nonionic surfactant in tetrahydrofuran to prepare a 0.2 wt % solution, filtering the solution through a 0.45 μm membrane filter, and measuring the resultant solution under the following conditions using gel permeation chromatography (GPC). Measuring device: HLC-8220GPC (Tosoh Corporation) Column: TSKgel G1000H (Tosoh Corporation), TSKgel G2000H (Tosoh Corporation) Eluent: tetrahydrofuran (THF) Elution rate: 0.3ml / min Detector: RI (polarity (+)) Column temperature: 40℃
[0050] The content of the nonionic surfactant in the xanthogen compound dispersion of the present invention is not particularly limited, but is preferably 0.1 to 30 parts by weight, more preferably 1 to 20 parts by weight, even more preferably 1.2 to 15 parts by weight, particularly preferably 1.5 to 10 parts by weight, and most preferably 2 to 5 parts by weight, relative to 100 parts by weight of the xanthogen compound.
[0051] The ratio of the anionic surfactant having no polyoxyalkylene structure to the nonionic surfactant in the xanthogen compound dispersion of the present invention is preferably 99:1 to 10:90, more preferably 97:3 to 15:85, even more preferably 95:5 to 55:45, particularly preferably 90:10 to 55:45, and most preferably 85:15 to 70:30, in terms of the weight ratio of "anionic surfactant having no polyoxyalkylene structure:nonionic surfactant". By setting the ratio of the anionic surfactant having no polyoxyalkylene structure to the nonionic surfactant within the above range, the dispersibility of the xanthogen compound in the xanthogen compound dispersion can be further improved, and the tensile strength and tear strength of the resulting film molded product such as a dip molded product can be further improved, and the stability of the tensile strength and tear strength can be further improved.
[0052] The water or alcohol used in the present invention is preferably at least one selected from water, methanol, ethanol, propanol and butanol, and more preferably water. That is, the xanthogen compound dispersion of the present invention is preferably an aqueous dispersion.
[0053] As a method for producing the xanthogen compound dispersion of the present invention, a method is preferably used in which an anionic surfactant not having a polyoxyalkylene structure, a nonionic surfactant, and water or alcohol are mixed, and then the resulting mixture is subjected to a crushing treatment. Here, the crushing treatment may be any treatment that can break down or relax the aggregation of the xanthogen compound contained in the dispersion, and is not particularly limited. For example, a method using a crushing device that utilizes a shearing action or a grinding action, a method using a stirring type crushing device, or the like, may be used. Specifically, a crushing device such as a roll mill, a hammer mill, a vibration mill, a jet mill, a ball mill, a planetary ball mill, a bead mill, a sand mill, or a three-roll mill may be used. Among these, a method of performing the crushing treatment using a ball mill, a planetary ball mill, or a bead mill is preferable.
[0054] For example, when the disintegration treatment is performed using a ball mill, it is preferable to use media having a media size of preferably φ5 to φ50 mm, more preferably φ10 to φ35 mm, at a rotation speed of preferably 10 to 300 rpm, more preferably 10 to 100 rpm, and for a treatment time of preferably 24 to 120 hours, more preferably 24 to 72 hours. When the disintegration treatment is performed using a planetary ball mill, it is preferable to use media having a media size of preferably φ0.1 to φ5 mm, more preferably φ0.3 to φ3 mm, at a rotation speed of preferably 100 to 1000 rpm, more preferably 100 to 500 rpm, and for a treatment time of preferably 0.25 to 5 hours, more preferably 0.25 to 3 hours. Furthermore, when the disintegration treatment is carried out using a bead mill, it is preferable to use media having a media size of preferably φ0.1 to φ3 mm, more preferably φ0.1 to φ1 mm, and to carry out the disintegration treatment under conditions of a rotation speed of preferably 1000 to 10000 rpm, more preferably 1000 to 5000 rpm, and a treatment time of preferably 0.25 to 5 hours, more preferably 0.25 to 3 hours.
[0055] <Conjugated diene polymer latex composition> The conjugated diene polymer latex composition of the present invention contains a latex of a conjugated diene polymer, a vulcanizing agent, and the above-mentioned xanthogen compound dispersion of the present invention.
[0056] The conjugated diene polymer constituting the latex of the conjugated diene polymer is not particularly limited, and examples thereof include synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), deproteinized natural rubber, and nitrile group-containing conjugated diene copolymer. Among these, synthetic polyisoprene, SIS, deproteinized natural rubber, and other isoprene units are preferred, and synthetic polyisoprene is particularly preferred. The conjugated diene polymer may be an acid-modified conjugated diene polymer obtained by modification with a monomer having an acidic group.
[0057] When synthetic polyisoprene is used as the conjugated diene polymer, the synthetic polyisoprene may be a homopolymer of isoprene or a copolymer of isoprene and other ethylenically unsaturated monomers copolymerizable therewith. The content of isoprene units in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and particularly preferably 100% by weight (homopolymer of isoprene) based on the total monomer units, since it is easy to obtain a membrane molded product such as a dip molded product that is flexible and has excellent tensile strength.
[0058] Examples of other ethylenically unsaturated monomers copolymerizable with isoprene include conjugated diene monomers other than isoprene, such as butadiene, chloroprene, and 1,3-pentadiene; ethylenically unsaturated nitrile monomers, such as acrylonitrile, methacrylonitrile, fumaronitrile, and α-chloroacrylonitrile; vinyl aromatic monomers, such as styrene and alkylstyrene; ethylenically unsaturated carboxylate monomers, such as methyl (meth)acrylate (meaning "methyl acrylate and / or methyl methacrylate", hereinafter the same applies to ethyl (meth)acrylate, etc.), ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; and the like. These other ethylenically unsaturated monomers copolymerizable with isoprene may be used alone or in combination.
[0059] Synthetic polyisoprene can be obtained by a conventional method, for example, by solution polymerization of isoprene and other copolymerizable ethylenically unsaturated monomers, which are used as necessary, in an inert polymerization solvent using a Ziegler-based polymerization catalyst made of trialkylaluminum-titanium tetrachloride or an alkyl lithium polymerization catalyst such as n-butyl lithium or sec-butyl lithium. The polymer solution of synthetic polyisoprene obtained by solution polymerization may be used as it is for the production of synthetic polyisoprene latex, but after solid synthetic polyisoprene is taken out from the polymer solution, it can be dissolved in an organic solvent and used for the production of synthetic polyisoprene latex. In addition, when a polymer solution of synthetic polyisoprene is obtained by the above-mentioned method, impurities such as the residue of the polymerization catalyst remaining in the polymer solution may be removed. In addition, an anti-aging agent, which will be described later, may be added to the solution during or after polymerization. In addition, commercially available solid synthetic polyisoprene may be used.
[0060] There are four types of isoprene units in synthetic polyisoprene, depending on the bonding state of isoprene: cis bond unit, trans bond unit, 1,2-vinyl bond unit, and 3,4-vinyl bond unit. From the viewpoint of improving the tensile strength of the obtained film molded article such as a dip molded article, the content of cis bond units in the isoprene units contained in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more, based on the total isoprene units.
[0061] The weight-average molecular weight of the synthetic polyisoprene is preferably 10,000 to 5,000,000, more preferably 500,000 to 5,000,000, and even more preferably 800,000 to 3,000,000, as calculated based on standard polystyrene by gel permeation chromatography analysis. By setting the weight-average molecular weight of the synthetic polyisoprene within the above range, the tensile strength of a film-formed product such as a dip-formed product is improved, and the synthetic polyisoprene latex tends to be easily produced.
[0062] The polymer Mooney viscosity (ML1+4, 100° C.) of the synthetic polyisoprene is preferably 50-85, more preferably 60-85, and further preferably 70-85.
[0063] Examples of methods for obtaining synthetic polyisoprene latex include (1) a method in which a solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an anionic surfactant, and the organic solvent is removed as necessary to produce a synthetic polyisoprene latex; and (2) a method in which isoprene alone or a mixture of isoprene and an ethylenically unsaturated monomer copolymerizable therewith is emulsion polymerized or suspension polymerized in the presence of an anionic surfactant to directly produce a synthetic polyisoprene latex. Among these, the above-mentioned production method (1) is preferred because it can use synthetic polyisoprene having a high ratio of cis-bond units in the isoprene units and can easily produce a film molded product such as a dip molded product having excellent mechanical properties such as tensile strength.
[0064] Examples of the organic solvent used in the above production method (1) include aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc.; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, cyclohexene, etc.; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, etc.; halogenated hydrocarbon solvents such as methylene chloride, chloroform, ethylene dichloride, etc. Among these, alicyclic hydrocarbon solvents are preferred, and cyclohexane is particularly preferred.
[0065] The amount of the organic solvent used is preferably 2,000 parts by weight or less, more preferably 20 to 1,500 parts by weight, and even more preferably 500 to 1,500 parts by weight, based on 100 parts by weight of the synthetic polyisoprene.
[0066] Examples of the anionic surfactant used in the production method (1) above include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, and sodium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium cetylbenzenesulfonate, and potassium cetylbenzenesulfonate; alkylsulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctyl sulfosuccinate; alkyl sulfates such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfates such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; and monoalkyl phosphates such as sodium lauryl phosphate and potassium lauryl phosphate.
[0067] Among these anionic surfactants, fatty acid salts, alkylbenzenesulfonates, alkylsulfosuccinates, alkyl sulfates and polyoxyethylene alkyl ether sulfates are preferred, with fatty acid salts and alkylbenzenesulfonates being particularly preferred.
[0068] In addition, it is preferable to use at least one selected from the group consisting of alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt, and polyoxyethylene alkyl ether sulfate salt in combination with a fatty acid salt, since it is possible to more efficiently remove a trace amount of polymerization catalyst (particularly aluminum and titanium) derived from synthetic polyisoprene and to suppress the generation of aggregates during the production of a conjugated diene polymer latex composition, and it is particularly preferable to use an alkylbenzenesulfonate in combination with a fatty acid salt. Here, as the fatty acid salt, sodium rosinate and potassium rosinate are preferable, and as the alkylbenzenesulfonate, sodium dodecylbenzenesulfonate and potassium dodecylbenzenesulfonate are preferable. In addition, these surfactants may be used alone or in combination of two or more.
[0069] As described above, by using at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates in combination with a fatty acid salt, the obtained latex contains at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates, and a fatty acid salt.
[0070] In the above-mentioned production method (1), a surfactant other than the anionic surfactant may be used in combination. Examples of such surfactant other than the anionic surfactant include copolymerizable surfactants such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers.
[0071] The amount of the anionic surfactant used in the above-mentioned (1) production method is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, based on 100 parts by weight of synthetic polyisoprene. When two or more types of surfactants are used, it is preferable that the total amount of these surfactants is within the above range. That is, for example, when at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate ester salt, and polyoxyethylene alkyl ether sulfate ester salt is used in combination with a fatty acid salt, it is preferable that the total amount of these surfactants is within the above range. If the amount of the anionic surfactant used is too small, a large amount of aggregates may be generated during emulsification, and conversely, if it is too large, it may become easy to foam, and pinholes may be generated in the obtained film molded product such as a dip molded product.
[0072] In addition, when at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate is used in combination with a fatty acid salt as an anionic surfactant, the weight ratio of the fatty acid salt to the total of at least one surfactant selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate is preferably in the range of 1:1 to 10:1, more preferably in the range of 1:1 to 7:1. If the ratio of the at least one surfactant selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate is too high, there is a risk of foaming becoming intense when handling the synthetic polyisoprene, which requires operations such as leaving it for a long time or adding an antifoaming agent, which may lead to deterioration of workability and increased costs.
[0073] The amount of water used in the above production method (1) is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, relative to 100 parts by weight of the organic solvent solution of synthetic polyisoprene. The type of water used may be hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc., with soft water, ion-exchanged water, and distilled water being preferred.
[0074] The device for emulsifying the solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an anionic surfactant is not particularly limited, and can be any device that is commercially available as an emulsifier or disperser. The method for adding the anionic surfactant to the solution or fine suspension of synthetic polyisoprene is not particularly limited, and it may be added in advance to either water or the solution or fine suspension of synthetic polyisoprene, or both, or it may be added to the emulsion during the emulsification operation, or it may be added all at once or in portions.
[0075] Examples of emulsifying devices include batch emulsifying machines such as "Homogenizer" (manufactured by IKA), "Polytron" (manufactured by Kinematica), and "TK Auto Homo Mixer" (manufactured by Tokushu Kika Kogyo); "TK Pipeline Homo Mixer" (manufactured by Tokushu Kika Kogyo), "Colloid Mill" (manufactured by Kobe Steel Pantech), "Thrasher" (manufactured by Nippon Coke & Engineering Co., Ltd.), "Trigonal Wet Fine Grinding Mill" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), "Cavitron" (manufactured by Eurotech), and Examples of such machines include continuous emulsifiers such as "Milder" (manufactured by Pacific Machinery & Engineering Co., Ltd.) and "Fine Flow Mill" (manufactured by Pacific Machinery & Engineering Co., Ltd.); high-pressure emulsifiers such as "Microfluidizer" (manufactured by Mizuho Kogyo Co., Ltd.), "Nanomizer" (manufactured by Nanomizer Co., Ltd.), and "APV Gaulin" (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as "Membrane Emulsifier" (manufactured by Reika Kogyo Co., Ltd.); vibration emulsifiers such as "Vibro Mixer" (manufactured by Reika Kogyo Co., Ltd.); and ultrasonic emulsifiers such as "Ultrasonic Homogenizer" (manufactured by Branson Co., Ltd.). The conditions for the emulsification operation using an emulsification device are not particularly limited, and the processing temperature, processing time, and the like may be appropriately selected so as to achieve the desired dispersion state.
[0076] In the above-mentioned production method (1), it is desirable to remove the organic solvent from the emulsion obtained through the emulsification operation. As a method for removing the organic solvent from the emulsion, a method capable of reducing the content of the organic solvent (preferably an alicyclic hydrocarbon solvent) in the obtained synthetic polyisoprene latex to 500 ppm by weight or less is preferable, and for example, a method such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted.
[0077] In the above method (1), it is preferable to obtain a synthetic polyisoprene latex by removing the organic solvent from the emulsion obtained through the emulsification operation. The method for removing the organic solvent from the emulsion is not particularly limited as long as it is a method that can reduce the total content of the alicyclic hydrocarbon solvent and the aromatic hydrocarbon solvent as the organic solvent in the obtained synthetic polyisoprene latex to 500 ppm by weight or less, and methods such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted.
[0078] After removing the organic solvent, if necessary, in order to increase the solid content concentration of the synthetic polyisoprene latex, a concentration operation may be carried out by a method such as reduced pressure distillation, normal pressure distillation, centrifugation, membrane concentration or the like. In particular, from the viewpoint of increasing the solid content concentration of the synthetic polyisoprene latex and reducing the amount of residual surfactant in the synthetic polyisoprene latex, it is preferable to carry out centrifugation.
[0079] Centrifugation is preferably carried out using a continuous centrifuge under the conditions of a centrifugal force of preferably 100 to 10,000 G, a solids concentration of the synthetic polyisoprene latex before centrifugation of preferably 2 to 15% by weight, a flow rate of the centrifuge of preferably 500 to 1700 kg / hr, and a back pressure (gauge pressure) of the centrifuge of preferably -0.05 to 1.6 MPa, more preferably 0.03 to 1.6 MPa, and a synthetic polyisoprene latex can be obtained as a light liquid after centrifugation. This can reduce the amount of surfactant remaining in the synthetic polyisoprene latex.
[0080] The solid content of the synthetic polyisoprene latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight. If the solid content is too low, the solid content of the conjugated diene polymer latex composition is low, so that the thickness of the obtained film molded product such as a dip molded product becomes thin and easily breaks. On the other hand, if the solid content is too high, the viscosity of the synthetic polyisoprene latex becomes high, so that it may be difficult to transport it through piping or to stir it in a mixing tank.
[0081] The volume average particle diameter of the synthetic polyisoprene latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and further preferably 0.5 to 2.0 μm. By setting the volume average particle diameter within the above range, the latex viscosity becomes appropriate and easy to handle, and also the formation of a film on the surface of the latex during storage of the synthetic polyisoprene latex can be suppressed.
[0082] The synthetic polyisoprene latex may also contain additives that are commonly used in the field of latex, such as a pH adjuster, an antifoaming agent, a preservative, a crosslinking agent, a chelating agent, an oxygen scavenger, a dispersant, and an antiaging agent. Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, alkali metal bicarbonates such as sodium bicarbonate, ammonia, and organic amine compounds such as trimethylamine and triethanolamine, with alkali metal hydroxides or ammonia being preferred.
[0083] As described above, the conjugated diene polymer may be a styrene-isoprene-styrene block copolymer (SIS), where "S" represents a styrene block and "I" represents an isoprene block.
[0084] SIS can be obtained by a conventional method, for example, block copolymerization of isoprene and styrene in an inert polymerization solvent using an active organic metal such as n-butyl lithium as an initiator. The obtained SIS polymer solution may be used as it is for the production of SIS latex, but after removing solid SIS from the polymer solution, the solid SIS can be dissolved in an organic solvent and used for the production of SIS latex. There is no particular limitation on the method for producing SIS latex, but a method is preferred in which a solution or fine suspension of SIS dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of a surfactant, and the organic solvent is removed as necessary to produce SIS latex. At this time, impurities such as the residue of the polymerization catalyst remaining in the polymer solution after synthesis may be removed. In addition, an antiaging agent, which will be described later, may be added to the solution during or after polymerization. In addition, commercially available solid SIS can be used.
[0085] As the organic solvent, the same one as in the case of the synthetic polyisoprene can be used, and aromatic hydrocarbon solvents and alicyclic hydrocarbon solvents are preferred, with cyclohexane and toluene being particularly preferred. The amount of the organic solvent used is usually 50 to 2,000 parts by weight, preferably 80 to 1,000 parts by weight, more preferably 100 to 500 parts by weight, and even more preferably 150 to 300 parts by weight, based on 100 parts by weight of the SIS.
[0086] Examples of the surfactant include the same surfactants as those in the case of the synthetic polyisoprene described above, and anionic surfactants are preferred, with sodium rosinate and sodium dodecylbenzenesulfonate being particularly preferred.
[0087] The amount of the surfactant used is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, based on 100 parts by weight of SIS. If the amount is too small, the stability of the latex tends to be poor, whereas if the amount is too large, foaming tends to occur, which may cause problems during dip molding.
[0088] The amount of water used in the above-mentioned method for producing SIS latex is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, based on 100 parts by weight of the SIS organic solvent solution. The type of water used may include hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc. Also, a polar solvent, typified by an alcohol such as methanol, may be used in combination with water.
[0089] The method of adding the monomer can be exemplified by the same method as in the case of the synthetic polyisoprene. The device for emulsifying the organic solvent solution or fine suspension of SIS in water in the presence of a surfactant can be exemplified by the same method as in the case of the synthetic polyisoprene. The method of adding the surfactant is not particularly limited, and it can be added in advance to either water or the organic solvent solution or fine suspension of SIS, or both, or it can be added to the emulsion during the emulsification operation, or it can be added all at once or in portions.
[0090] In the above-mentioned method for producing SIS latex, it is preferable to obtain SIS latex by removing the organic solvent from the emulsion obtained through the emulsification operation. The method for removing the organic solvent from the emulsion is not particularly limited, and methods such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted.
[0091] After removing the organic solvent, the SIS latex may be concentrated by vacuum distillation, atmospheric distillation, centrifugation, membrane concentration or the like, if necessary, in order to increase the solids concentration of the SIS latex.
[0092] The solid content of the SIS latex is preferably 30 to 70% by weight, more preferably 50 to 70% by weight. If the solid content is too low, the solid content of the conjugated diene polymer latex composition is low, so that when the composition is made into a film such as a dip-molded product, the film thickness becomes thin and the film is easily broken. On the other hand, if the solid content is too high, the viscosity of the SIS latex becomes high, making it difficult to transport the composition through piping or to stir the composition in a mixing tank.
[0093] The SIS latex may contain additives that are generally used in the field of latex, such as a pH adjuster, an antifoaming agent, a preservative, a crosslinking agent, a chelating agent, an oxygen scavenger, a dispersant, and an antioxidant. Examples of the pH adjuster include the same ones as those in the synthetic polyisoprene, and alkali metal hydroxides or ammonia are preferred.
[0094] The content of styrene units in the styrene block in the SIS contained in the SIS latex thus obtained is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and even more preferably 100% by weight, based on the total monomer units. The content of isoprene units in the isoprene block in the SIS is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and even more preferably 100% by weight, based on the total monomer units.
[0095] The content ratio of styrene units and isoprene units in SIS, in terms of the weight ratio of "styrene units:isoprene units", is usually in the range of 1:99 to 90:10, preferably 3:97 to 70:30, more preferably 5:95 to 50:50, and further preferably 10:90 to 30:70.
[0096] The weight-average molecular weight of the SIS, calculated as standard polystyrene by gel permeation chromatography analysis, is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 100,000 to 300,000. By setting the weight-average molecular weight of the SIS within the above range, the balance between the tensile strength and flexibility of a film-formed product such as a dip-formed product is improved, and the production of a SIS latex tends to be easier.
[0097] The volume average particle diameter of the latex particles (SIS particles) in the SIS latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and further preferably 0.5 to 2.0 μm. By setting the volume average particle diameter of the latex particles within the above range, the viscosity of the latex becomes appropriate, making it easy to handle, and also preventing a film from being formed on the surface of the latex during storage of the SIS latex.
[0098] As the conjugated diene polymer, natural rubber from which proteins have been removed can also be used. As the natural rubber that is the raw material for the natural rubber from which proteins have been removed, natural rubber contained in latex obtained from natural rubber trees and natural rubber contained in latex obtained by treating such latex can be used, for example, natural rubber contained in field latex harvested from natural rubber trees and natural rubber contained in commercially available natural rubber latex obtained by treating field latex with ammonia or the like can be used.
[0099] The method for removing proteins from natural rubber when obtaining deproteinized natural rubber is not particularly limited, but natural rubber latex can be reacted with a urea compound in the presence of a surfactant to denature the proteins contained in the natural rubber, and then the natural rubber latex containing such denatured proteins can be subjected to processes such as centrifugation, coagulation of the rubber component, ultrafiltration, etc. to separate the natural rubber from the denatured proteins, and the denatured proteins can be removed to obtain deproteinized natural rubber latex.
[0100] As the conjugated diene polymer, a nitrile group-containing conjugated diene copolymer can also be used, as described above.
[0101] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing a conjugated diene monomer with an ethylenically unsaturated nitrile monomer, and may also be a copolymer obtained by copolymerizing, in addition to the above, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.
[0102] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, and chloroprene. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content of the conjugated diene monomer unit formed by the conjugated diene monomer in the nitrile group-containing conjugated diene copolymer is preferably 56 to 78% by weight, more preferably 56 to 73% by weight, and even more preferably 56 to 68% by weight. By setting the content of the conjugated diene monomer unit within the above range, the obtained film molded product such as a dip molded product can be excellent in texture and elongation.
[0103] The ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, and the like. Among them, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The content ratio of the ethylenically unsaturated nitrile monomer unit formed by the ethylenically unsaturated nitrile monomer in the nitrile group-containing conjugated diene copolymer is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and even more preferably 30 to 40% by weight. By setting the content of the ethylenically unsaturated nitrile monomer unit within the above range, the obtained film molded product such as a dip molded product can be excellent in texture and elongation.
[0104] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include ethylenically unsaturated carboxylic acid monomers, which are ethylenically unsaturated monomers containing a carboxyl group; vinyl aromatic monomers such as styrene, alkylstyrene, and vinylnaphthalene; fluoroalkyl vinyl ethers such as fluoroethyl vinyl ether; ethylenically unsaturated amide monomers such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, and N-propoxymethyl (meth)acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, and fumarate. Examples of the ethylenically unsaturated carboxylic acid ester monomers include dibutyl acrylate, diethyl maleate, methoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, cyanomethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; and crosslinkable monomers such as divinylbenzene, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate. These ethylenically unsaturated monomers can be used alone or in combination of two or more. In addition, by using an ethylenically unsaturated carboxylic acid monomer as the other copolymerizable ethylenically unsaturated monomer, the nitrile group-containing conjugated diene copolymer can be provided with a carboxyl group.
[0105] The ethylenically unsaturated carboxylic acid monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a carboxyl group, and examples thereof include ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polyvalent carboxylic acid monomers such as itaconic acid, maleic acid, and fumaric acid; ethylenically unsaturated polyvalent carboxylic acid anhydrides such as maleic anhydride and citraconic anhydride; ethylenically unsaturated polyvalent carboxylic acid partial ester monomers such as monobutyl fumarate, monobutyl maleate, and mono-2-hydroxypropyl maleate; and the like. Among these, ethylenically unsaturated monocarboxylic acids are preferred, and methacrylic acid is particularly preferred. These ethylenically unsaturated carboxylic acid monomers can also be used as alkali metal salts or ammonium salts. Moreover, the ethylenically unsaturated carboxylic acid monomers can be used alone or in combination of two or more. The content of ethylenically unsaturated carboxylic acid monomer units formed by ethylenically unsaturated carboxylic acid monomers in the nitrile group-containing conjugated diene copolymer is preferably 2 to 5% by weight, more preferably 2 to 4.5% by weight, and further preferably 2.5 to 4.5% by weight. By setting the content of the ethylenically unsaturated carboxylic acid monomer units within the above range, the obtained film molded article such as a dip molded article can be excellent in texture and elongation.
[0106] In the nitrile group-containing conjugated diene copolymer, the content of other monomer units formed by other ethylenically unsaturated monomers is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less.
[0107] The nitrile group-containing conjugated diene copolymer can be obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, and a method of copolymerizing by emulsion polymerization is preferred. As the emulsion polymerization method, a conventionally known method can be adopted.
[0108] The number average particle size of the latex of the nitrile group-containing conjugated diene copolymer is preferably 60 to 300 nm, more preferably 80 to 150 nm. The particle size can be adjusted to a desired value by, for example, adjusting the amounts of the emulsifier and polymerization initiator used.
[0109] As described above, the conjugated diene polymer used in the present invention may be synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), deproteinized natural rubber, or nitrile group-containing conjugated diene copolymer, but is not limited thereto. A butadiene polymer, a styrene-butadiene copolymer, or the like may also be used.
[0110] The butadiene polymer may be a homopolymer of 1,3-butadiene as a conjugated diene monomer, or a copolymer obtained by copolymerizing 1,3-butadiene as a conjugated diene monomer with another ethylenically unsaturated monomer that is copolymerizable with the conjugated diene monomer.
[0111] The styrene-butadiene copolymer is a copolymer obtained by copolymerizing styrene with 1,3-butadiene as a conjugated diene monomer, and may also be a copolymer obtained by copolymerizing, in addition to these, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.
[0112] The conjugated diene polymer used in the present invention may be an acid-modified conjugated diene polymer obtained by modification with a monomer having an acidic group, and is preferably a carboxy-modified carboxy-modified conjugated diene polymer. The carboxy-modified conjugated diene polymer can be obtained by modifying the above-mentioned conjugated diene polymer with a monomer having a carboxyl group. In addition, when an ethylenically unsaturated carboxylic acid monomer is used as the possible other ethylenically unsaturated monomer for the nitrile group-containing conjugated diene copolymer, the copolymer is already carboxy-modified, and therefore modification with a monomer having a carboxyl group, which will be described later, is not necessarily required.
[0113] The method for modifying a conjugated diene polymer with a monomer having a carboxyl group is not particularly limited, but for example, a method of graft polymerizing a monomer having a carboxyl group onto a conjugated diene polymer in an aqueous phase can be mentioned. The method for graft polymerizing a monomer having a carboxyl group onto a conjugated diene polymer in an aqueous phase is not particularly limited, and a conventionally known method may be used, but for example, a method of adding a monomer having a carboxyl group and a graft polymerization catalyst to a latex of a conjugated diene polymer, and then reacting the monomer having a carboxyl group with the conjugated diene polymer in an aqueous phase is preferred.
[0114] The graft polymerization catalyst is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-t-butyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate; and the like. From the viewpoint of further improving the tensile strength of the resulting film molded body such as a dip molded body, organic peroxides are preferred, and 1,1,3,3-tetramethylbutyl hydroperoxide is particularly preferred. These graft polymerization catalysts may be used alone or in combination of two or more.
[0115] The above graft polymerization catalysts can be used alone or in combination of two or more kinds. The amount of the graft polymerization catalyst used varies depending on the type, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight, based on 100 parts by weight of the conjugated diene polymer. The method of adding the graft polymerization catalyst is not particularly limited, and known methods of addition such as lump-sum addition, divided addition, and continuous addition can be used.
[0116] In addition, the organic peroxide can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but examples thereof include compounds containing reduced metal ions such as ferrous sulfate and cuprous naphthenate; sulfinates such as sodium hydroxymethanesulfinate; and amine compounds such as dimethylaniline. These reducing agents may be used alone or in combination of two or more.
[0117] The amount of the reducing agent to be added is not particularly limited, but is preferably 0.01 to 1 part by weight per 1 part by weight of the organic peroxide.
[0118] The method of adding the organic peroxide is not particularly limited, and any known method of addition such as lump-sum addition, divided addition, continuous addition, etc. may be used.
[0119] The reaction temperature when reacting the conjugated diene polymer with the monomer having a carboxyl group is not particularly limited, but is preferably 15 to 80° C., more preferably 30 to 50° C. The reaction time when reacting the conjugated diene polymer with the monomer having a carboxyl group may be appropriately set depending on the reaction temperature, but is preferably 30 to 300 minutes, more preferably 60 to 120 minutes.
[0120] When the conjugated diene polymer is reacted with a monomer having a carboxyl group, the solid content concentration of the latex of the conjugated diene polymer is not particularly limited, but is preferably 5 to 60% by weight, more preferably 10 to 40% by weight.
[0121] Examples of monomers having a carboxyl group include ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polycarboxylic acid monomers such as itaconic acid, maleic acid, fumaric acid, and butene tricarboxylic acid; partial ester monomers of ethylenically unsaturated polycarboxylic acids such as monobutyl fumarate, monobutyl maleate, and mono 2-hydroxypropyl maleate; and polycarboxylic anhydrides such as maleic anhydride and citraconic anhydride. Since the effect of carboxy modification is more pronounced, ethylenically unsaturated monocarboxylic acid monomers are preferred, and acrylic acid and methacrylic acid are particularly preferred. These monomers may be used alone or in combination of two or more. The carboxyl group also includes salts with alkali metals, ammonia, and the like.
[0122] The amount of the monomer having a carboxyl group used is preferably 0.01 to 100 parts by weight, more preferably 0.01 to 40 parts by weight, and further preferably 0.5 to 20 parts by weight, based on 100 parts by weight of the conjugated diene polymer. By setting the amount of the monomer having a carboxyl group used within the above range, the viscosity of the obtained conjugated diene polymer latex composition becomes more appropriate, making it easier to transfer, and the tensile strength of the obtained film molded product such as a dip molded product is further improved.
[0123] The method of adding the monomer having a carboxyl group to the latex of the conjugated diene polymer is not particularly limited, and any known addition method such as lump-sum addition, divided addition, continuous addition, etc. can be used.
[0124] The modification rate of the carboxy-modified conjugated diene polymer with a monomer having a carboxyl group may be appropriately controlled depending on the intended use of the resulting conjugated diene polymer latex composition, but is preferably 0.01 to 10% by weight, more preferably 0.2 to 5% by weight, further preferably 0.3 to 3% by weight, and particularly preferably 0.4 to 2% by weight. The modification rate is represented by the following formula. Modification rate (wt%) = (X / Y) x 100 In the above formula, X represents the weight of the monomer unit having a carboxyl group in the carboxy-modified conjugated diene polymer, and Y represents the weight of the carboxy-modified conjugated diene polymer. 1 H-NMR measurement was performed. 1 It can be determined by a method of calculation from the results of H-NMR measurement, or a method of determining the amount of acid by neutralization titration and then calculating from the determined amount of acid.
[0125] The latex of the conjugated diene polymer (including an acid-modified conjugated diene polymer) used in the present invention may contain additives that are usually added in the field of latexes, such as a pH adjuster, an antifoaming agent, a preservative, a chelating agent, an oxygen scavenger, a dispersant, and an antioxidant.
[0126] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; and organic amine compounds such as trimethylamine and triethanolamine; with alkali metal hydroxides or ammonia being preferred.
[0127] The solid content of the latex of the conjugated diene polymer (including an acid-modified conjugated diene polymer) used in the present invention is preferably 30 to 70% by weight, more preferably 40 to 70% by weight. By setting the solid content within the above range, the generation of aggregates in the latex can be more effectively suppressed, and the separation of polymer particles during storage of the latex can be more effectively suppressed.
[0128] The conjugated diene polymer latex composition of the present invention contains the above-mentioned xanthogen compound dispersion of the present invention and a vulcanizing agent in addition to the above-mentioned conjugated diene polymer latex.
[0129] The amount of the xanthogen compound dispersion in the conjugated diene polymer latex composition of the present invention is not particularly limited, but the content of the xanthogen compound relative to 100 parts by weight of the conjugated diene polymer is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, and even more preferably 0.5 to 5 parts by weight. By setting the amount of the xanthogen compound dispersion in the above range, the tensile strength and tear strength of the obtained film molded product such as a dip molded product can be further increased, and the stability of the tensile strength and tear strength can be further increased.
[0130] The xanthogen compound contained in the xanthogen compound dispersion may be present in the form of a xanthogen salt due to the action of an activator contained in the conjugated diene polymer latex composition of the present invention, resulting in the conjugated diene polymer latex composition containing two or more kinds of xanthogen compounds. Alternatively, when the conjugated diene polymer latex composition contains sulfur as a sulfur-based vulcanizing agent or the like, the xanthogen compound may be present in the conjugated diene polymer latex composition in part in the form of a xanthogen disulfide or xanthogen polysulfide due to the action of sulfur.
[0131] As the vulcanizing agent, a sulfur-based vulcanizing agent is preferably used. Examples of the sulfur-based vulcanizing agent include powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, and other sulfur; sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, caprolactam disulfide (N,N'-dithio-bis(hexahydro-2H-azepinone-2)), phosphorus-containing polysulfide, polymer polysulfide, and sulfur-containing compounds such as 2-(4'-morpholinodithio)benzothiazole. Among these, sulfur is preferably used. The sulfur-based vulcanizing agent can be used alone or in combination of two or more.
[0132] The content of the vulcanizing agent in the latex composition of the present invention is not particularly limited, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight, and further preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the conjugated diene polymer. By setting the content of the vulcanizing agent within the above range, the tensile strength of the obtained film molded product such as a dip molded product can be increased while suppressing an increase in hardness.
[0133] In addition, the conjugated diene polymer latex composition of the present invention preferably further contains a metal oxide and / or a typical metal compound, and more preferably contains at least a metal oxide.
[0134] The metal oxide and the typical metal compound act as an activator when used together with the xanthogen compound contained in the xanthogen compound dispersion. In addition, when an acid-modified conjugated diene polymer is used as the conjugated diene polymer, the metal oxide and the typical metal compound also act as a crosslinking agent for crosslinking acidic groups, thereby making it possible to further increase the tensile strength and tear strength of the resulting film-formed product, such as a dip-formed product.
[0135] The metal oxide is not particularly limited, but may be zinc oxide, magnesium oxide, titanium oxide, calcium oxide, lead oxide, iron oxide, copper oxide, tin oxide, nickel oxide, chromium oxide, cobalt oxide, or aluminum oxide. Among these, zinc oxide is preferred from the viewpoint of further improving the tensile strength and tear strength of the resulting film molded product such as a dip molded product. These metal oxides may be used alone or in combination.
[0136] The typical metal compound is not particularly limited as long as it is a typical metal compound other than oxide, but includes hydroxides, carbonates, sulfates, nitrates, phosphates, chlorides, bromides, iodides, etc. of typical metals, and among them, carbonates of typical metals are preferred. Also, typical metal compounds include compounds of zinc, magnesium, calcium, lead, tin, and aluminum, and among them, zinc compounds are preferred. Among these, zinc carbonate is preferred from the viewpoint of further improving the tensile strength and tear strength of the obtained film molded body such as a dip molded body. These typical metal compounds may be used alone or in combination.
[0137] The total content of the metal oxide and / or typical metal compound in the conjugated diene polymer latex composition of the present invention is not particularly limited, but is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 10 parts by weight, and further preferably 0.5 to 5 parts by weight, based on 100 parts by weight of the conjugated diene polymer. By setting the total content of the metal oxide and / or typical metal compound within the above range, the tensile strength and tear strength of the obtained film molded product such as a dip molded product can be further improved.
[0138] The conjugated diene polymer latex composition of the present invention may further contain a vulcanization accelerator other than the xanthogen compound, so long as it is within a range that can suppress the occurrence of delayed-type allergy (Type IV) symptoms in the obtained film molded article such as a dip molded article. The content of the vulcanization accelerator other than the xanthogen compound is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 0% by weight (i.e., no vulcanization accelerator other than the xanthogen compound is contained) based on the total amount of the content of the xanthogen compound and the content of the vulcanization accelerator other than the xanthogen compound.
[0139] As the vulcanization accelerator other than the xanthogen compound, those usually used in film forming such as dip molding can be used, for example, dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, dibenzyldithiocarbamic acid, and zinc salts thereof; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole zinc salt; Examples of suitable vulcanization accelerators include lead, 2-mercaptothiazoline, dibenzothiazyl disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthio carbamoylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholino dithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, and 1,3-bis(2-benzothiazyl mercaptomethyl)urea. However, from the viewpoint of appropriately suppressing the occurrence of symptoms of delayed-type allergy (Type IV), it is preferable to use a vulcanization accelerator other than a thiuram-based vulcanization accelerator, a dithiocarbamate-based vulcanization accelerator, or a thiazole-based vulcanization accelerator. Note that the vulcanization accelerators other than xanthogen compounds can be used alone or in combination of two or more.
[0140] The conjugated diene polymer latex composition of the present invention may further contain additives such as antioxidants, dispersants, reinforcing agents such as carbon black, silica, and talc, fillers such as calcium carbonate and clay, ultraviolet absorbers, and plasticizers, as required.
[0141] Antioxidants include 2,6-di-4-methylphenol, 2,6-di-t-butylphenol, butyl hydroxyanisole, 2,6-di-t-butyl-α-dimethylamino-p-cresol, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, styrenated phenol, 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-methylenebis(2,6-di-t-butylphenyl)propionate, butyl hydroxyanisole ... phenol-based antioxidants not containing sulfur atoms, such as 2,2'-methylene-bis(4-methyl-6-t-butylphenol), alkylated bisphenols, and butylated products of p-cresol and dicyclopentadiene; 2,2'-thiobis-(4-methyl-6-t-butylphenol), 4,4'-thiobis-(6-t-butyl-o-cresol), 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-trimethyl-2-phenylpropanediol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), alkylated bisphenols, and butylated products of p-cresol and dicyclopentadiene; Thiobisphenol-based antioxidants such as (triazin-2-ylamino)phenol; phosphite ester-based antioxidants such as tris(nonylphenyl)phosphite, diphenylisodecylphosphite, and tetraphenyldipropylene glycol diphosphite; sulfur ester-based antioxidants such as dilauryl thiodipropionate; phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonylamido)-diphenyla amine-based antioxidants such as amine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, butyraldehyde-aniline condensate, quinoline-based antioxidants such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, hydroquinone-based antioxidants such as 2,5-di-(t-amyl)hydroquinone, etc. These antioxidants can be used alone or in combination of two or more.
[0142] The content of the antioxidant in the conjugated diene polymer latex composition of the present invention is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, based on 100 parts by weight of the carboxy-modified conjugated diene polymer.
[0143] The method for preparing the conjugated diene polymer latex composition of the present invention is not particularly limited, but may be, for example, a method of mixing the vulcanizing agent, the xanthogen compound dispersion, and various compounding agents used as necessary with the above-mentioned conjugated diene polymer latex, etc. In this case, a method of preparing an aqueous dispersion of compounding components other than the conjugated diene polymer latex, and then mixing the aqueous dispersion with the conjugated diene polymer latex, etc. may also be adopted.
[0144] The solid content concentration of the conjugated diene polymer latex composition of the present invention is preferably 10 to 60% by weight, more preferably 10 to 55% by weight.
[0145] In the present invention, from the viewpoint of obtaining sufficient mechanical properties of a film-formed product such as a dip-molded product, it is preferable to perform aging (pre-vulcanization) of the conjugated diene polymer latex composition of the present invention before subjecting it to film forming such as dip molding. The aging (pre-vulcanization) time is not particularly limited, but is preferably 8 to 120 hours, more preferably 24 to 72 hours. The aging (pre-vulcanization) temperature is not particularly limited, but is preferably 20 to 40°C. In addition, when using the conjugated diene polymer latex composition of the present invention, after performing aging (pre-vulcanization) for a predetermined time, film forming such as dip molding may be continuously performed while maintaining the aging (pre-vulcanization) conditions (while continuing aging (pre-vulcanization)), and in this case, the aging (pre-vulcanization) time and the aging (pre-vulcanization) temperature may be within the above range. In particular, since the conjugated diene polymer latex composition of the present invention contains the xanthogen compound dispersion of the present invention described above, even if the maturation (pre-vulcanization) time is relatively long as described above, a film molding excellent in tensile strength and tear strength can be obtained, and even if a large number of film moldings such as dip moldings are continuously produced while maintaining the maturation (pre-vulcanization) conditions, a film molding excellent in tensile strength and tear strength can be stably produced (it can be stably produced without a large decrease in tensile strength and tear strength).As a result, according to the conjugated diene polymer latex composition of the present invention, a film molding such as a dip molding excellent in tensile strength and tear strength can be produced with high productivity.
[0146] <Film-molded body> The film molded article of the present invention is a film-shaped molded article made of the above-mentioned conjugated diene polymer latex composition of the present invention. The film molded article of the present invention has a thickness of preferably 0.03 to 0.50 mm, more preferably 0.05 to 0.40 mm, and particularly preferably 0.08 to 0.30 mm.
[0147] The film molded article of the present invention is not particularly limited, but is preferably a dip molded article obtained by dip molding the conjugated diene polymer latex composition of the present invention. Dip molding is a method in which a mold is immersed in a conjugated diene polymer latex composition, the composition is deposited on the surface of the mold, the mold is then removed from the composition, and the composition deposited on the surface of the mold is then dried. The mold before being immersed in the conjugated diene polymer latex composition may be preheated. Furthermore, a coagulant may be used as necessary before the mold is immersed in the conjugated diene polymer latex composition or after the mold is removed from the conjugated diene polymer latex composition.
[0148] Specific examples of the method of using a coagulant include a method of immersing a mold before immersion in the conjugated diene polymer latex composition in a solution of the coagulant to adhere the coagulant to the mold (anodic coagulation immersion method) and a method of immersing a mold on which the conjugated diene polymer latex composition has been deposited in a coagulant solution (Teague coagulation immersion method). Of these, the anodic coagulation immersion method is preferred in that it gives a dip-molded product with less thickness unevenness.
[0149] Specific examples of the coagulant include water-soluble polyvalent metal salts such as metal halides, such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates, such as barium nitrate, calcium nitrate, and zinc nitrate; acetates, such as barium acetate, calcium acetate, and zinc acetate; and sulfates, such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Among these, calcium salts are preferred, and calcium nitrate is more preferred. These water-soluble polyvalent metal salts can be used alone or in combination of two or more.
[0150] The coagulant can usually be used as a solution of water, alcohol, or a mixture thereof, and is preferably used in the form of an aqueous solution. This aqueous solution may further contain a water-soluble organic solvent such as methanol or ethanol, or a nonionic surfactant. The concentration of the coagulant varies depending on the type of water-soluble polyvalent metal salt, but is preferably 5 to 50% by weight, more preferably 10 to 30% by weight.
[0151] After the mold is removed from the conjugated diene polymer latex composition, the deposit formed on the mold is usually dried by heating under appropriately selected drying conditions.
[0152] Next, the dip-molded layer thus obtained is subjected to a heat treatment to be vulcanized. In addition, before the heat treatment, the layer may be immersed in water, preferably in warm water at 30 to 70°C, for about 1 to 60 minutes to remove water-soluble impurities (for example, excess emulsifier, coagulant, etc.). The operation of removing the water-soluble impurities may be performed after the dip-molded layer is heat-treated, but is preferably performed before the heat treatment in order to remove the water-soluble impurities more efficiently.
[0153] The dip-molded layer is usually vulcanized by a heat treatment at a temperature of 80 to 150° C., preferably for 10 to 130 minutes. The heating method may be external heating using infrared rays or heated air, or internal heating using high frequency waves. Of these, external heating using heated air is preferred.
[0154] The dip-molded layer is then removed from the dip-molding mold to obtain a dip-molded body in the form of a film. The method of removal can be a method of peeling it off from the mold by hand or by using water pressure or compressed air pressure. After removal, a heat treatment may be further performed at a temperature of 60 to 120°C for 10 to 120 minutes.
[0155] The film molded article of the present invention may be obtained by any method other than the method of dip molding the conjugated diene polymer latex composition of the present invention as long as the conjugated diene polymer latex composition of the present invention can be molded into a film (for example, a coating method, etc.).
[0156] The film-formed article of the present invention including the dip-formed article of the present invention can suppress the occurrence of symptoms of delayed-type allergy (Type IV) in addition to immediate-type allergy (Type I), and is excellent in tensile strength and tear strength, and is excellent in stability of tensile strength and tear strength, and can be particularly suitably used as, for example, gloves. When the film-formed article is a glove, in order to prevent adhesion at the contact surface between the film-formed articles and to improve slippage when putting on and taking off the glove, inorganic fine particles such as talc or calcium carbonate or organic fine particles such as starch particles may be sprinkled on the glove surface, an elastomer layer containing fine particles may be formed on the glove surface, or the surface layer of the glove may be chlorinated.
[0157] Further, the film-formed article of the present invention including the dip-formed article of the present invention can be used not only for the above-mentioned gloves, but also for medical products such as baby bottle nipples, droppers, tubes, water pillows, balloon sacks, catheters, and condoms; toys such as balloons, dolls, and balls; industrial products such as pressure molding bags and gas storage bags; finger cots, etc.
[0158] <Adhesive composition> In the present invention, the above-mentioned conjugated diene polymer latex composition of the present invention can be used as an adhesive composition.
[0159] The content (solid content) of the conjugated diene polymer latex composition of the present invention in the adhesive composition is preferably 5 to 60% by weight, more preferably 10 to 30% by weight.
[0160] The adhesive composition preferably contains an adhesive resin in addition to the conjugated diene polymer latex composition of the present invention. The adhesive resin is not particularly limited, but for example, resorcin-formaldehyde resin, melamine resin, epoxy resin and isocyanate resin can be suitably used, and among these, resorcin-formaldehyde resin is preferred. As the resorcin-formaldehyde resin, a known one (for example, one disclosed in JP-A-55-142635) can be used. The reaction ratio of resorcin and formaldehyde is usually 1:1 to 1:5, preferably 1:1 to 1:3, in terms of the molar ratio of "resorcin:formaldehyde".
[0161] In order to further increase the adhesive strength of the adhesive composition, the adhesive composition may contain conventionally used 2,6-bis(2,4-dihydroxyphenylmethyl)-4-chlorophenol or similar compounds, isocyanates, blocked isocyanates, ethylene urea, polyepoxides, modified polyvinyl chloride resins, and the like.
[0162] Furthermore, the adhesive composition may contain a crosslinking aid. By containing a crosslinking aid, the mechanical strength of the composite obtained by using the adhesive composition, which will be described later, may be improved. Examples of the crosslinking aid include quinone dioximes such as p-quinone dioxime; methacrylic acid esters such as lauryl methacrylate and methyl methacrylate; allyl compounds such as DAF (diallyl fumarate), DAP (diallyl phthalate), TAC (triallyl cyanurate), and TAIC (triallyl isocyanurate); maleimide compounds such as bismaleimide, phenylmaleimide, and N,Nm-phenylenedimaleimide; sulfur; and the like. EXAMPLES
[0163] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In addition, the "parts" below are based on weight unless otherwise specified. In addition, various physical properties were measured as follows.
[0164] <Solid content concentration> 2 g of the sample was weighed out (weight: X2) onto an aluminum dish (weight: X1), and dried for 2 hours in a hot air dryer at 105° C. Then, after cooling in a desiccator, the weight of the aluminum dish was measured (weight: X3), and the solid content was calculated according to the following formula. Solid content concentration (wt%)=(X3-X1)×100 / X2
[0165] <Modification rate of carboxy-modified synthetic polyisoprene> The number of carboxyl groups in the carboxyl-modified synthetic polyisoprene constituting the latex of the carboxyl-modified synthetic polyisoprene was determined by neutralization titration using an aqueous sodium hydroxide solution. Then, based on the number of carboxyl groups thus determined, the modification rate by the monomer having a carboxyl group was calculated according to the following formula. Modification rate (wt%) = (X / Y) x 100 In the above formula, X represents the weight of the monomer unit having a carboxyl group in the carboxy-modified synthetic polyisoprene, and Y represents the weight of the carboxy-modified synthetic polyisoprene.
[0166] <Number average molecular weight (Mn) of nonionic surfactants> The nonionic surfactant was dissolved in tetrahydrofuran to prepare a 0.2 wt % solution, and then filtered through a 0.45 μm membrane filter to obtain a measurement sample. The measurement was performed using gel permeation chromatography (GPC) under the following conditions to determine the number average molecular weight (Mn) of the nonionic surfactant in terms of standard polystyrene. Measuring device: HLC-8220GPC (Tosoh Corporation) Column: TSKgel G1000H (Tosoh Corporation), TSKgel G2000H (Tosoh Corporation) Eluent: tetrahydrofuran (THF) Elution rate: 0.3ml / min Detector: RI (polarity (+)) Column temperature: 40℃
[0167] <Tensile strength and tensile strength stability of dip-molded body> The dip-molded bodies (24-hour aged products and 72-hour aged products) were punched out with a dumbbell (product name "Super Dumbbell (model: SDMK-100C)" manufactured by Dumbbell Co., Ltd.) based on ASTM D412 to prepare test specimens for tensile strength measurement. The test specimens were pulled at a tensile speed of 500 mm / min with a Tensilon universal testing machine (product name "RTG-1210" manufactured by Orientec Co., Ltd.) to measure the tensile strength (unit: MPa) immediately before breakage. The measurement was performed on five test specimens, and the median value of the measured values of the five test specimens (i.e., the tensile strength value of the test specimen showing the third largest value among the five test specimens) was adopted as the tensile strength value. It can be determined that the higher the tensile strength, the more excellent the tensile strength. Furthermore, the smaller the difference between the tensile strength of the product aged for 24 hours and the tensile strength of the product aged for 72 hours, the more excellent the stability of the tensile strength can be determined.
[0168] <Tear strength and tear strength stability of dip-molded products> The dip-molded bodies (24-hour aged products and 72-hour aged products) were left in a constant temperature and humidity room at 23°C and 50% relative humidity for 24 hours or more according to ASTM D624-00, and then punched out with a dumbbell (trade name "Die C", manufactured by Dumbbell Co., Ltd.) to prepare test pieces for measuring tear strength. The test pieces were pulled at a tensile speed of 500 mm / min with a Tensilon universal testing machine (trade name "RTG-1210", manufactured by A&D Co., Ltd.) to measure tear strength (unit: N / mm). The measurement was performed on five test pieces, and the median value of the measured values of the five test pieces (i.e., the tear strength value of the test piece that showed the third largest value among the five test pieces) was adopted as the tear strength value. The higher the tear strength, the better the tear strength. Furthermore, the smaller the difference between the tear strength of the product aged for 24 hours and the tear strength of the product aged for 72 hours, the more excellent the stability of the tear strength can be determined.
[0169] <Production Example 1> (Production of carboxy-modified synthetic polyisoprene latex) Synthetic polyisoprene with a weight average molecular weight of 1,300,000 (product name "NIPOL IR2200L", manufactured by Zeon Corporation, isoprene homopolymer, cis-bond unit content 98%) was mixed with cyclohexane and dissolved by heating to 60°C with stirring to prepare a cyclohexane solution of synthetic polyisoprene (a) with a viscosity of 12,000 mPa s as measured with a Brookfield viscometer (solids concentration 8% by weight).
[0170] On the other hand, 20 parts of sodium rosinate was added to water and dissolved by raising the temperature to 60° C. to prepare an aqueous solution of an anionic surfactant (b) with a concentration of 1.5% by weight.
[0171] Next, the cyclohexane solution (a) and the anionic surfactant aqueous solution (b) were mixed in a weight ratio of 1:1.5 using a mixer (product name "Multiline Mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.), and then mixed and emulsified at a rotation speed of 4100 rpm using an emulsifier (product name "Milder MDN310", manufactured by Pacific Machinery Co., Ltd.) to obtain an emulsion (c). At that time, the total feed flow rate of the cyclohexane solution (a) and the anionic surfactant aqueous solution (b) was 2,000 kg / hr, the temperature was 60° C., and the back pressure (gauge pressure) was 0.5 MPa.
[0172] Next, the emulsion (c) was heated to 80°C under reduced pressure of -0.01 to -0.09 MPa (gauge pressure) to distill off cyclohexane, and an aqueous dispersion of synthetic polyisoprene (d) was obtained. At this time, an antifoaming agent (product name "SM5515", manufactured by Dow Corning Toray Co., Ltd.) was continuously added while being sprayed so that the amount was 300 ppm by weight relative to the synthetic polyisoprene in the emulsion (c). When distilling off cyclohexane, the emulsion (c) was adjusted to 70% by volume or less of the tank volume, and stirring was performed slowly at 60 rpm using a three-stage inclined paddle impeller as the stirring impeller.
[0173] After the distillation of cyclohexane was completed, the obtained synthetic polyisoprene aqueous dispersion (d) was centrifuged at 4,000 to 5,000 G using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) to obtain a synthetic polyisoprene latex (e) as a light liquid. The centrifugation conditions were as follows: solid content concentration of the aqueous dispersion (d) before centrifugation was 10% by weight, flow rate during continuous centrifugation was 1300 kg / hr, and back pressure (gauge pressure) of the centrifuge was 1.5 MPa. The obtained synthetic polyisoprene latex (e) had a solid content concentration of 60% by weight.
[0174] Next, 130 parts of distilled water was added to 100 parts of synthetic polyisoprene in the obtained synthetic polyisoprene latex (e) to dilute it. Then, 0.8 parts of sodium salt of β-naphthalenesulfonic acid formalin condensate (trade name "Demol T-45", manufactured by Kao Corporation) as a dispersant was diluted with 4 parts of distilled water per 100 parts of synthetic polyisoprene to the synthetic polyisoprene latex (e) over 5 minutes. Next, the synthetic polyisoprene latex (e) to which the dispersant was added was charged in a nitrogen-substituted reaction vessel equipped with a stirrer, and the temperature was heated to 30°C while stirring. In addition, a methacrylic acid dilution solution was prepared by mixing 3 parts of methacrylic acid as a monomer having a carboxyl group and 16 parts of distilled water using another vessel. This methacrylic acid dilution solution was added to a reaction vessel heated to 30°C over 30 minutes.
[0175] Furthermore, a solution (f) consisting of 7 parts of distilled water, 0.32 parts of sodium formaldehyde sulfoxylate (trade name "SFS", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.01 parts of ferrous sulfate (trade name "Frost Fe", manufactured by Chubu Chelest Co., Ltd.) was prepared using another container. After transferring this solution (f) into a reaction container, 0.5 parts of 1,1,3,3-tetramethylbutyl hydroperoxide (trade name "Perocta H", manufactured by Nippon Oil & Fats Co., Ltd.) was added and reacted at 30°C for 1 hour to obtain a latex of carboxy-modified synthetic polyisoprene. The carboxy-modified synthetic polyisoprene was then concentrated using a centrifuge to obtain a light liquid with a solid content concentration of 55%. The modification rate of the obtained latex of carboxy-modified synthetic polyisoprene by a monomer having a carboxyl group was measured according to the above method, and the modification rate was 0.5% by weight.
[0176] <Production Example 2> (Manufacture of SIS latex) Except for using SIS (product name "Quintac 3620", manufactured by Zeon Corporation) instead of synthetic polyisoprene having a weight average molecular weight of 1,300,000, the same procedure as in Production Example 1 was carried out to obtain a SIS latex as emulsion (c). The solid content of the obtained SIS latex was 60% by weight.
[0177] <Example 1> (Preparation of Xanthogen Compound Dispersion) A xanthogen compound dispersion was obtained by mixing and disintegrating 2.5 parts of zinc diisopropyl xanthate (trade name "Noxeler ZIX", manufactured by Ouchi Shinko Chemical Industry Co., Ltd., volume average particle size: 14 μm, 95% volume cumulative diameter (D95): 55 μm), 0.22 parts of sodium salt of β-naphthalenesulfonic acid formalin condensate (trade name "Demol T-45", manufactured by Kao Corporation, weight average molecular weight: 7,000) as an anionic surfactant having no polyoxyalkylene structure, 0.06 parts of polyoxyethylene oleyl ether (trade name "Emulgen 404", manufactured by Kao Corporation, number average molecular weight (Mn): 421) as a nonionic surfactant using a ball mill (trade name "Magnet Ball Mill", manufactured by Nitto Kagaku Co., Ltd.). The mixing conditions for the ball mill were as follows: φ15mm and φ20mm ceramic porcelain balls were used, and the ball mill was rotated at 50 rpm for 72 hours or more. The volume average particle size and 95% volume cumulative diameter (D95) of zinc diisopropylxanthate in the resulting xanthogen compound dispersion were measured using a laser diffraction scattering particle size distribution meter (product name "SALD-2300", manufactured by Shimadzu Corporation), and the volume average particle size of zinc diisopropylxanthate was 2.1 μm, and the 95% volume cumulative diameter (D95) was 3.8 μm.
[0178] (Preparation of Latex Composition) First, a styrene-maleic acid mono-sec-butyl ester-maleic acid monomethyl ester polymer (trade name "Scripset550", manufactured by Hercules) was prepared, and sodium hydroxide was used to neutralize 100% of the carboxyl groups in the polymer to prepare a sodium salt aqueous solution (concentration 10% by weight). Then, this sodium salt aqueous solution was added to the latex of the carboxy-modified synthetic polyisoprene obtained in Production Example 1 so that the amount of the sodium salt aqueous solution was 0.8 parts in terms of solid content per 100 parts of the carboxy-modified synthetic polyisoprene in the latex, and a mixture was obtained.
[0179] Then, while stirring the resulting mixture, the xanthogen compound dispersion prepared above was added so that the amount of zinc diisopropylxanthogenate added was 2.5 parts per 100 parts of the carboxy-modified synthetic polyisoprene in the mixture.
[0180] Next, aqueous dispersions of each compounding agent were added so that the total solid content was 1.5 parts of zinc oxide, 1.5 parts of sulfur, and 2 parts of antioxidant (product name "Wingstay L", manufactured by Goodyear Chemical Industries, Ltd.) to obtain a latex composition. The obtained latex composition was divided into two, and one was aged (pre-vulcanized) for 24 hours in a thermostatic water bath adjusted to 25°C, and the other was aged (pre-vulcanized) for 72 hours in a thermostatic water bath adjusted to 25°C to obtain a latex composition aged for 24 hours and a latex composition aged for 72 hours.
[0181] (Production of dip-molded body) A commercially available ceramic hand mold (manufactured by Shinko Co., Ltd.) was washed and preheated in an oven at 70°C, then immersed in an aqueous coagulant solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "Emulgen 109P", manufactured by Kao Co., Ltd.) for 5 seconds and removed from the aqueous coagulant solution. The hand mold was then dried in an oven at 70°C for 30 minutes or more to allow the coagulant to adhere to the hand mold, thereby coating the hand mold with the coagulant.
[0182] The hand mold covered with the coagulant was then removed from the oven and immersed in the 24-hour aged latex composition obtained above for 10 seconds. The hand mold was then air-dried at room temperature for 10 minutes, and then immersed in 60°C warm water for 5 minutes to dissolve water-soluble impurities, forming a dip-molded layer on the hand mold. The dip-molded layer formed on the hand mold was then vulcanized by heating in an oven at a temperature of 130°C for 30 minutes, cooled to room temperature, and talc was sprayed on it before peeling it off from the hand mold to obtain a glove-shaped dip-molded product (24-hour aged product). In addition, a glove-shaped dip-molded product (72-hour aged product) was obtained in the same manner as above, except that a 72-hour aged latex composition was used instead of the 24-hour aged latex composition. The tensile strength and tear strength of the obtained dip-molded products (24-hour aged product and 72-hour aged product) were measured according to the above method. The results are shown in Table 1.
[0183] <Example 2> Except for changing the amount of the sodium salt of β-naphthalenesulfonic acid formalin condensate to 0.14 parts and the amount of polyoxyethylene oleyl ether to 0.14 parts, a xanthogen compound dispersion was obtained in the same manner as in Example 1. The volume average particle diameter and 95% volume cumulative diameter (D95) of zinc diisopropylxanthogenate in the obtained xanthogen compound dispersion were measured in the same manner as in Example 1, and the volume average particle diameter of zinc diisopropylxanthogenate was 2.3 μm and the 95% volume cumulative diameter (D95) was 3.9 μm. Then, except for using the obtained xanthogen compound dispersion, a 24-hour aged latex composition, a 72-hour aged latex composition, and dip-molded products (products aged for 24 hours and 72 hours) were obtained in the same manner as in Example 1, and measurements were performed in the same manner. The results are shown in Table 1.
[0184] <Example 3> Except for changing the amount of sodium salt of β-naphthalenesulfonic acid formalin condensate to 0.06 parts and the amount of polyoxyethylene oleyl ether to 0.22 parts, a xanthogen compound dispersion was obtained in the same manner as in Example 1. The volume average particle diameter and 95% volume cumulative diameter (D95) of zinc diisopropylxanthogenate in the obtained xanthogen compound dispersion were measured in the same manner as in Example 1, and the volume average particle diameter of zinc diisopropylxanthogenate was 2.8 μm and the 95% volume cumulative diameter (D95) was 4.4 μm. Then, except for using the obtained xanthogen compound dispersion, a 24-hour aged latex composition, a 72-hour aged latex composition, and dip-molded products (products aged for 24 hours and 72 hours) were obtained in the same manner as in Example 1, and measurements were performed in the same manner. The results are shown in Table 1.
[0185] <Example 4> A xanthogen compound dispersion was obtained in the same manner as in Example 1, except that 0.06 parts of polyoxyethylene octyldodecyl ether (product name "EMULGEN 2025G", manufactured by Kao Corporation, number average molecular weight (Mn): 2450) was used instead of 0.06 parts of polyoxyethylene oleyl ether. The volume average particle diameter and 95% volume cumulative diameter (D95) of zinc diisopropyl xanthogenate in the obtained xanthogen compound dispersion were measured in the same manner as in Example 1, and the volume average particle diameter of zinc diisopropyl xanthogenate was 2.3 μm and the 95% volume cumulative diameter (D95) was 3.8 μm. Then, except for using the obtained xanthogen compound dispersion, a 24-hour aged latex composition, a 72-hour aged latex composition, and dip-molded products (products aged for 24 hours and 72 hours) were obtained in the same manner as in Example 1, and measurements were performed in the same manner. The results are shown in Table 1.
[0186] <Example 5> Except for using the SIS latex obtained in Production Example 2 instead of the carboxy-modified synthetic polyisoprene latex obtained in Production Example 1, the 24-hour aged latex composition, the 72-hour aged latex composition, and the dip-molded products (24-hour aged products and 72-hour aged products) were obtained in the same manner as in Example 4, and measurements were performed in the same manner. The results are shown in Table 1.
[0187] <Comparative Example 1> Except for changing the amount of sodium salt of β-naphthalenesulfonic acid formalin condensate to 0.28 parts and not using polyoxyethylene oleyl ether, a xanthogen compound dispersion was obtained in the same manner as in Example 1. The volume average particle diameter and 95% volume cumulative diameter (D95) of zinc diisopropylxanthogenate in the obtained xanthogen compound dispersion were measured in the same manner as in Example 1, and the volume average particle diameter of zinc diisopropylxanthogenate was 2.1 μm and the 95% volume cumulative diameter (D95) was 3.8 μm. Then, except for using the obtained xanthogen compound dispersion, a 24-hour aged latex composition, a 72-hour aged latex composition, and dip-molded products (products aged for 24 hours and 72 hours) were obtained in the same manner as in Example 1, and measurements were performed in the same manner. The results are shown in Table 1.
[0188] [Table 1]
[0189] As shown in Table 1, by using a xanthogen compound dispersion containing a xanthogen compound, an anionic surfactant not having a polyoxyalkylene structure, a nonionic surfactant, and water or alcohol as a vulcanization accelerator, a vulcanization product can be obtained without using a vulcanization accelerator (such as a thiuram-based vulcanization accelerator, a dithiocarbamate-based vulcanization accelerator, or a thiazole-based vulcanization accelerator) that causes the symptoms of delayed-type allergy (Type IV), and the occurrence of symptoms of delayed-type allergy (Type IV) in addition to immediate-type allergy (Type I) can be suppressed. Furthermore, the obtained dip-molded product had excellent tensile strength and tear strength, and was excellent in stability of tensile strength and tear strength. In addition, according to the above xanthogen compound dispersion, even when the dip-molded product production is started after the obtained latex composition is aged for 24 hours and the dip-molded product production is continued for 48 hours or more while maintaining the aging conditions, the dip-molded product excellent in tensile strength and tear strength can be stably produced. That is, the obtained latex composition has excellent aging stability (Examples 1 to 5).
[0190] On the other hand, when a xanthogen compound dispersion not containing a nonionic surfactant was used, the obtained dip-molded article had poor stability in tensile strength and tear strength (Comparative Example 1).
Claims
1. A xanthogen compound dispersion containing a xanthogen compound, an anionic surfactant having no polyoxyalkylene structure, a nonionic surfactant, and water or an alcohol, the content of the anionic surfactant not having a polyoxyalkylene structure is 1 to 30 parts by weight based on 100 parts by weight of the xanthogen compound, The xanthogen compound dispersion has a content of the nonionic surfactant of 1 to 30 parts by weight based on 100 parts by weight of the xanthogen compound.
2. The xanthogen compound dispersion according to claim 1, wherein a ratio of the anionic surfactant not having a polyoxyalkylene structure to the nonionic surfactant is 99:1 to 10:90 in terms of a weight ratio of "anionic surfactant not having a polyoxyalkylene structure:nonionic surfactant."
3. 3. The xanthogen compound dispersion according to claim 1, wherein the anionic surfactant having no polyoxyalkylene structure is an aromatic compound.
4. 4. The xanthogen compound dispersion according to claim 1, wherein the nonionic surfactant has a number average molecular weight of 100 to 5,000.
5. A conjugated diene polymer latex composition comprising a latex of a conjugated diene polymer, a vulcanizing agent, and the xanthogen compound dispersion according to any one of claims 1 to 4, The content of the xanthogen compound in the xanthogen compound dispersion is 0.1 to 10 parts by weight based on 100 parts by weight of the conjugated diene polymer.
6. The conjugated diene polymer latex composition according to claim 5, further comprising a metal oxide and / or a typical metal compound.
7. 7. The conjugated diene polymer latex composition according to claim 5, wherein the conjugated diene polymer is synthetic polyisoprene, a styrene-isoprene-styrene block copolymer, or deproteinized natural rubber.
8. A film formed from the conjugated diene polymer latex composition according to any one of claims 5 to 7.
9. A dip-molded article comprising the conjugated diene polymer latex composition according to any one of claims 5 to 7.
10. An adhesive composition comprising the conjugated diene polymer latex composition according to any one of claims 5 to 7.
Citation Information
Patent Citations
Water-base adhesive composition and bonded structure using the same
JP2004359787A
Aqueous adhesive composition and method of manufacturing wet suit material
JP2012158694A
JPP7415933B
JPP7435457B
JPP7521534B